Romania : First Review under the Stand-By Arrangement and Request for Modification of Performance Criteria-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report, 2011)
Romania's economy has stabilized and growth is now resuming. The financial program's objectives include structural reforms in the energy and transport sectors, and restructuring and privatization of state-owned enterprises (SOEs). The macroeconomic outlook is expected to improve in 2011-12 with a gradual pickup in growth, a stable current account, and inflationary pressures that are still high but will begin to recede after mid-2011. The authorities are also focusing on reducing the arrears of the rest of the public sector.